New Directions in the Search for the First Floridians - Garrison, Ervan G.; Thulman, David Kelley (Book collections on Project MUSE., 2019)
New Directions in the Search for the First Floridians grew out of the First Floridians conference held in October 2015 in Monticello, Florida, which focused on the state and future of Paleoindian studies in Florida but also reached temporally into the Early Archaic period and beyond Florida into the greater Southeast and as far west as Texas. This volume is organized into three sections: The past, present, and future of the archaeology of early Floridians, early Floridian studies in a broader context, and technological advances in the study of early Floridians.